The influence of fertilizers on the damage of spring barley plants by intrastalk pests and grain yield - Kuzmenko, N. (Quarantine and plant protection, 2022)
Goal. To study the population and harmfulness of intrastalk pests in the agrocenosis of spring barley depending on the use of fertilizers. Methods. The investigations was carried out in a stationary field, fixed nine-course-fallow-grain-row crop rotation at the Department for Plant Production and Cultivar Investigations of the Plant Production Institute named after V.Ya. Yuriev of the National Academy of Sciences (Eastern Forest-Steppe of Ukraine) during 2011—20. Results. During the years of research, the species composition of intrastalk pests was represented by: Oscinella pusilla Mg., O. frit L., Chaetocnema hortensis Geoffr., and Mayetiola destructor Say. Oscinella pusilla Mg. and O. frit L. dominated, damage to shoots by their larvae varied from 1.9% (2016) to 61.1% (2013). Damage to shoots by Chaetocnema hortensis Geoffr. larvae ranged from 0.4% (2015) to 35.5% (2011). The greatest damage to shoots by the larvae of Mayetiola destructor Say. was registered in 2018 — 5.7%. Application of fertilizers (manure 6.6 t/ha of the crop rotation area, aftereffect, and mineral fertilizers in the norm N30P30K30 or N45P45K45) provided increased resistance of spring barley plants to damage by pests. On the average over 2011…2020 year period, in the block without fertilizers, damage to shoots by Oscinella pusilla Mg. and O. frit L. larvae was 21.6%, in the fertilized block — 19.3% (decrease at the tendency level). At the tillering stage, the undamaged shoots on the background without fertilizers was 72.5%, on the fertilized background — 76.1% (difference at the tendency level). A reliable converse average correlation was established between the damage of shoots by intrastalk pests and the grain yield of spring barley (r = –0.5). Averaged over ten years, the grain yield in the block without fertilizers was 3.25 t/ha, with the application of fertilizers — 4.69 t/ha, there was a difference of 30.7%. Conclusions. The positive role of fertilizers in regulating the number of intrastalk pests of spring barley and increasing grain yield was established.